UMKM Desa Kurungdahu Berdayasaing Melalui Pendampingan Berkelanjutan - Nurhaula Huddin, Muhammad; Nafiudin; Wajdi, Farid (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The traditional MSME product, semprong cake, has the potential to be developed and can become a leading commodity in Kurungdahu Village. However, observations and interviews have revealed several partner issues, including limited financial record-keeping, lack of managerial skills, and restricted market access. The primary focus of this community service program is to provide socialization and assistance, both theoretically and practically, in the development of semprong cake products and the utilization of technology to market the products more broadly. The goal of this service is to transform semprong cake into an MSME that can boost the economy in Kurungdahu Village. The methods used to achieve this goal include ongoing observation and mentoring, enabling MSMEs to benefit from the preparation of simple financial reports, branding, packaging, and marketing assistance through social media to increase sales.